Episodic simple shear tests to measure strength changes for whole-life geotechnical design. Issue 1 (8th March 2021) - Laham, N.I.; Kwa, K.A.; White, D.J.; Gourvenec, S.M.
Abstract : This technical note describes a set of direct simple shear (DSS) tests that characterise the evolving geotechnical properties of a soft soil, through a loading history that represents episodic loading and consolidation periods as encountered by some offshore infrastructure. The interpretation uses a critical state soil mechanics (CSSM) framework. CSSM provides the necessary building blocks to quantify the balance between undrained cyclic loading and the associated increases in pore pressure, and drainage and consolidation, leading to strength regain. The results show how DSS tests can characterise the through-life response of soft clays. The measured responses showed the changing strength of the clay due to consolidation effects following loading, and match predictions from simple models. The results show how DSS tests can characterise the types of behaviour also seen in centrifuge models and field penetrometer tests related to the long-term response of soft clays under offshore infrastructure.